2020
DOI: 10.1103/physrevb.101.020415
|View full text |Cite
|
Sign up to set email alerts
|

Transient response of the spin Peltier effect revealed by lock-in thermoreflectance measurements

Abstract: a) E-mail: IGUCHI.Ryo@nims.go.jp [Abstract] Transient response of the spin Peltier effect (SPE) in a Pt/yttrium iron garnet junction system has been investigated by means of a lock-in thermoreflectance method. We applied an alternating charge current to the Pt layer to drive SPE through the spin Hall effect, and measured the AC response of the resultant SPE-induced temperature modulation at frequencies ranging from 10 Hz to 1 MHz. We found that the SPE-induced temperature modulation decreases with increasin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…In fact, the characteristic length for SPE in Fig. 4(b) is comparable to that estimated in the previous SPE experiments 24,26,27) but smaller than that estimated in the previous SSE experiments. 15,[29][30][31][32][33] This situation indicates that the Onsager reciprocal relation between SPE and SSE is not simple and its magnon frequency dependence should be taken into account.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In fact, the characteristic length for SPE in Fig. 4(b) is comparable to that estimated in the previous SPE experiments 24,26,27) but smaller than that estimated in the previous SSE experiments. 15,[29][30][31][32][33] This situation indicates that the Onsager reciprocal relation between SPE and SSE is not simple and its magnon frequency dependence should be taken into account.…”
supporting
confidence: 75%
“…The l SPE value near room temperature (314 K) is estimated to be 0.9 μm, which is comparable to the values obtained in the previous studies on SPE. 24,26,27) We found that l SPE remains almost constant as the temperature increases. Next, we compare the T dependence of the SPE signal with that of the SSE voltage.…”
mentioning
confidence: 64%
“…The Onsager reciprocal of SSE is the spin Peltier effect (SPE). [4][5][6][7][8][9][10][11] A typical system used for studying SPE and SSE is paramagnetic metal Pt/ferrimagnetic insulator yttrium iron garnet (YIG) junction systems, [3][4][5]7,[12][13][14][15] where the spin and heat currents are carried by electron spins in Pt and magnons in YIG. [16][17][18][19] SPE and SSE are characterized by their length scale including the magnon-spin diffusion length l m and the magnon-phonon thermalization length l mp in YIG.…”
mentioning
confidence: 99%
“…The SPE-induced temperature modulation appears only within the wires and the thermal diffusion is suppressed. This is attributable to the dipolar heat sources placed near the sample surface by the SPE 35,39,43 . Figure 2g shows A SPE as a function of y D in the left Cu-Ir wire with t = 30 nm.…”
Section: Resultsmentioning
confidence: 99%